Peran Kesiapan untuk Berubah terhadap Kinerja Guru di Masa Pandemi Covid-19 - Novitasari, Dewiana; Asbari, Masduki (Journal of Industrial Engineering & Management Research, 2020)
This study aimed to measure the effect of transformational leadership on teacher performance of the teachers of the five private schools in Tangerang which are mediated by readiness for change. Data collection was done by a simple random sampling technique and the returned and valid questionnaire results were 221 samples. Data processing was used the SEM method with SmartPLS 3.0 software. The results of this study concluded that transformational leadership has no significant effect on teacher performance, but transformational leadership has a positive and significant effect on readiness for change. This study conclude also that readiness for change has a positive and significant effect on the relationship between transformational leadership and teacher performance. Readiness for change as a full mediator. This new research proposed a model for building teacher performance among the teachers of the private schools in Tangerang through enhancing transformational leadership practice with readiness for change as a mediator. This research could pave the way to improve teacher readiness in facing the era of education 4.0.